2018
DOI: 10.1089/dia.2017.0250
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump and Continuous Glucose Monitor Initiation in Hospitalized Patients with Type 2 Diabetes Mellitus

Abstract: Insulin pump and CGM initiation are feasible during hospitalization, although they are labor intensive. Although insulin pump initiation may not lead to improved glycemic control, there is a trend toward CGM detecting a greater number of hypoglycemic episodes. Larger studies are needed to determine whether use of this technology can lower inpatient morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…A UK study of 80 000 examinees showed that several years are needed for intensification of medication treatment in type 2 diabetes patients, and the time range is longer when an insulin-dependent patient takes more different medications. Additional research in the UK has shown that many doctors delay changing a treatment, which can cause complications with diabetes and permanent consequences for the patient (e.g., cerebrovascular stroke, amputations, neuropathy, nephropathy, and retinopathy) [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A UK study of 80 000 examinees showed that several years are needed for intensification of medication treatment in type 2 diabetes patients, and the time range is longer when an insulin-dependent patient takes more different medications. Additional research in the UK has shown that many doctors delay changing a treatment, which can cause complications with diabetes and permanent consequences for the patient (e.g., cerebrovascular stroke, amputations, neuropathy, nephropathy, and retinopathy) [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing or reporting on missing data are scarce. However, within controlled standardized settings or inpatient studies of short duration, a minimal loss of data has been reported ranging from 0 up to 24% when using various sensor technologies [5,34,[37][38][39][40][41][42]. The 4% of missing measurement nights correspond with those numbers and are within the 5% boundary for feasibility.…”
Section: Feasibilitymentioning
confidence: 92%
“…Table 1 summarizes the literature for insulin pump therapy from the outpatient to inpatient setting, and initiation during a hospitalization. [18][19][20][21][22][23][24][25][26]…”
Section: Insulin Pump Management In the Inpatient Setting And Transmentioning
confidence: 99%